Moral Values in Interstellar Movie: A Father-Daughter Relationship - Rahmah, Salwa Sabita (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2024)
ABSTRACT ENGLISH:This study investigates the moral values embedded in Christopher Nolan's film Interstellar, with the goal of identifying and analysing the ethical lessons conveyed by its narrative. The research employs a qualitative methodology, with an in-depth examination of key scenes that depict moral values. The study identifies eight key moral values in the film: honesty, bravery, protection, discipline, love and affection, kindness and friendliness, loyalty, and the complex father-daughter relationship. Each value is critically evaluated within the context of the storyline, emphasizing its impact on the characters' decisions and the film's overall message. To uncover and interpret the moral values embedded in specific scenes of Interstellar, the researcher used Linda and Eyre's (1993) theoretical framework from